Effective VLSs in Language Learning: An Analysis of Micro Strategy Use. - Yılmaz, Vesile Gül; Çöker, Berna (Electronic Turkish Studies, 2021)
The purpose of this research was to investigate the micro VLSs Turkish graduate learners with high vocabulary levels employ, and thus to pinpoint the effective micro VLSs. The micro VLSs rarely or never used by most of the graduate learners with high vocabulary levels were also investigated to point out the least used micro VLSs. A descriptive research design was employed in the study. The participants were a total of 128 Turkish students pursuing their graduate (master’s and doctorate) education in Turkey (EFL) and the UK (ESL). Study data were collected via the ‘Vocabulary Learning Strategies Questionnaire’ and the ‘Vocabulary Levels Test’ after taking the necessary permissions from Exeter University Graduate School of Education Ethical Committee (with the reference number D/14/15/28) on 09/03/2015 and from Dokuz Eylul University Institude of Educational Sciences Ethical Committee (with the reference number 06) on 26/05/2016. The study data were analysed using descriptive statistics (mean, standard deviation, etc.) to determine the learners with high vocabulary levels. Strategies employed by high-level learners with top five rankings and those reported to be used either rarely or none at all by most of the participants were compared and contrasted in terms of their language learning context. A t test was also used to see if the difference in VLS use between the ELS and EFL contexts was statistically significant or not. The results revealed that the most popular VLSs among highlevel learners was ‘getting help from the context to guess word meaning’ and the least popular was ‘getting the teacher check the vocabulary notebooks, lists and word-cards prepared by the learner for accuracy’. There were also differences in the use of VLSs between the two contexts. In the light of the study findings, it is suggested that instruction of effective VLSs be considered as part of English language teaching practices. Differences between contexts should be taken into account and further investigated.